Control of center of mass motion during walking correlates with gait and balance in people with incomplete spinal cord injury - Dusane, Shamali; Shafer, Anna; Ochs, Wendy L.; Cornwell, Tara; Henderson, Heather; Kim, Kwang-Youn A.; Gordon, Keith E. (Frontiers in Neurology, 2023)
Background There is evidence that ambulatory people with incomplete spinal cord injury (iSCI) have an impaired ability to control lateral motion of their whole-body center of mass (COM) during walking. This impairment is believed to contribute to functional deficits in gait and balance, however that relationship is unclear. Thus, this cross-sectional study examines the relationship between the ability to control lateral COM motion during walking and functional measures of gait and balance in people with iSCI. Methods We assessed the ability to control lateral COM motion during walking and conducted clinical gait and balance outcome measures on 20 ambulatory adults with chronic iSCI (C1-T10 injury, American Spinal Injury Association Impairment Scale C or D). To assess their ability to control lateral COM motion, participants performed three treadmill walking trials. During each trial, real-time lateral COM position and a target lane were projected on the treadmill. Participants were instructed to keep their lateral COM position within the lane. If successful, an automated control algorithm progressively reduced the lane width, making the task more challenging. If unsuccessful, the lane width increased. The adaptive lane width was designed to challenge each participant’s maximum capacity to control lateral COM motion during walking. To quantify control of lateral COM motion, we calculated lateral COM excursion during each gait cycle and then identified the minimum lateral COM excursion occurring during five consecutive gait cycles. Our clinical outcome measures were Berg Balance Scale (BBS), Timed Up and Go test (TUG), 10-Meter Walk Test (10MWT) and Functional Gait Assessment (FGA). We used a Spearman correlation analysis (ρ) to examine the relationship between minimum lateral COM excursion and clinical measures. Results Minimum lateral COM excursion had significant moderate correlations with BBS (ρ = −0.54, p = 0.014), TUG (ρ = 0.59, p = 0.007), FGA (ρ = −0.59, p = 0.007), 10MWT-preferred (ρ = −0.59, p = 0.006) and 10MWT-fast (ρ = −0.68, p = 0.001). Conclusion Control of lateral COM motion during walking is associated with a wide range of clinical gait and balance measures in people with iSCI. This finding suggests the ability to control lateral COM motion during walking could be a contributing factor to gait and balance in people with iSCI.